Nexus Between Consumer Ethnocentrism and Purchase Intentions - Karki, Dipendra; Khadka, Upashan (Journal of Innovation in Academia, 2023)
The purpose of this study is to analyze the impact of Consumer Ethnocentrism (CE) on the purchase intention of fast-moving consumer goods (FMCG) in Kathmandu. The study involved the administration of a structured, close-ended questionnaire to 324 FMCG consumers aged between 13 and 65 residing in Kathmandu. The results indicate that consumer ethnocentrism and country-of-origin information significantly affect consumers' intentions to purchase foreign FMCG products by influencing their attitudes. The analysis of the Consumer Ethnocentrism Tendencies Scale (CETSCALE) and the results of partial least squares structural equation modeling (PL-SEM) reveal that FMCG consumers in Kathmandu tend to exhibit ethnocentric tendencies, prioritizing domestically made products and being mindful of the economic implications of relying on imports. Notably, young adults, particularly those with lower income levels, hold stronger ethnocentric beliefs than others. Additionally, the study finds that FMCG consumers actively seek country-of-origin information, with females displaying a higher likelihood of seeking such details. Moreover, consumer ethnocentrism and country-of-origin information jointly influence purchase intentions for foreign FMCG products through their distinct effects on consumers' attitudes toward foreign FMCG brands. These findings have significant implications for FMCG businesses and researchers interested in understanding consumer behavior dynamics in the market.